(untitled) (World Bulletin of Social Sciences, 2025)
In classical literature, a creator’s skill was assessed not by what they depicted but by how they depicted it. Thus, an artist’s talent was closely tied to their style of expression. Abdurauf Fitrat, a scholar well-versed in classical poetics, not only studied the theoretical foundations of aruz (classical prosody) and traditional rhyme but also presented his own perspectives on aesthetics (badi’) and its role in literary works. In his textbook Rules of Literature, he addresses artistic devices and their function in literary texts as part of the creator’s unique style.